Ella Bella ballerina and A Midsummer night's dream - Mayhew, James, 1964- (Barron's Educational Series, Inc., 2015)
"Ella's kindly ballet teacher, Madame Rosa, introduces the children to A Midsummer night's dream by Felix Mendelssohn. Ella is so inspired that she stays behind after class is over for just one more fairy dance . . .and finds herself transported into the story! . . . A brief passage at the back of the book tells the story of William Shakespeare's beloved comedy and includes some interesting facts about Felix Mendelssohn's enchanting music."--Book jacket.